The Politics of Embarrassment: Considerations on How Norm-Transgressions of Political Representatives Shape Nation-Wide Communication of Emotions on Social Media - Paulus, Frieder M.; Müller-Pinzler, Laura; Meshi, Dar; Peng, Tai-Quan; Martinez Mateo, Marina; Krach, Sören (Frontiers in Communication, 2019)
In this article, we hypothesize, and then demonstrate, that experiences of embarrassment have significantly increased in the United States, due in part, to the current situation in American politics under President Donald Trump. We provide support for our hypothesis by conducting both qualitative and quantitative analyses of Twitter posts in the U.S. obtained from the Crimson Hexagon database. Next, based on literature from social psychology, social neuroscience and political theory, we propose a two-step process explaining why Trump’s behavior has caused people in the U.S. to feel more embarrassment. First, compared to former representatives, Trump violates social norms in a manner that seems intentional, and second, these intentional norm violations specifically threaten the social integrity of in-group members — in this case, U.S. citizens. We discuss how these norm violations relate to the behavior of currently represented citizens and contextualize our rationale in recent changes of political representation and the public sphere. We conclude by proposing that more frequent, nation-wide experiences of embarrassment on behalf of the representative may motivate political actions to prevent further harm to individuals’ self-concepts and protect social integrity.